Rich-pore iron phosphate, lithium iron phosphate and preparation method of rich-pore iron phosphate and lithium iron phosphate
By preparing pore-rich iron phosphate and converting it into lithium iron phosphate by carbon thermal reduction method, the problem of degradation of lithium iron phosphate battery at low temperature is solved, and the preparation of lithium iron phosphate positive electrode material with excellent low temperature performance is achieved.
Patent Information
- Application Number
- CN202411584448.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
Lithium iron phosphate batteries exhibit lower specific capacity, serious attenuation and safety hazards at low temperatures, mainly due to their low conductivity and Li diffusion rate.
By controlling the process conditions of iron phosphate, pore-rich iron phosphate with rich pores and high specific surface area was prepared, and it was converted into lithium iron phosphate positive electrode material with excellent low temperature performance by carbon thermal reduction.
The durability of lithium iron phosphate positive electrode material under low temperature conditions of -40℃ has been achieved, reducing the cost of low-temperature performance research by enterprises, and avoiding the risk of using high-temperature and high-pressure containers.
Smart Images

Figure CN119461286A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a porous iron phosphate, lithium iron phosphate and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in small battery fields such as mobile consumer electronics, electric vehicle industry, and energy storage battery due to their high energy density, high voltage, good cycle performance, high power, stable performance, no memory effect, low self-discharge rate, wide operating temperature range, and environmental friendliness. Lithium iron phosphate cathode material has a theoretical specific capacity of 170mA·h / g, and has the advantages of good environmental protection, high thermal stability and cycle performance, and more guaranteed safety performance. It is an ideal cathode material for lithium-ion power batteries. However, compared with other cathode materials, low temperature has a more serious impact on the performance of lithium iron phosphate.
[0003] When used at low temperatures, lithium iron phosphate batteries will have serious problems such as a serious decrease in specific capacity, severe attenuation, and potential safety hazards. The main reason is that the conductivity and Li diffusion rate of lithium iron phosphate batteries are very low, so the low-temperature performance is poor. In order to obtain lithium iron phosphate materials with excellent low-temperature performance, there are two common ways. One is to use carbon thermal reduction to conduct modification research during the synthesis process of lithium iron phosphate materials, and the other is to synthesize by hydrothermal method. However, the carbon thermal reduction method often requires a lot of basic research to determine the elements and proportions of doping or coating. If the indicators of the iron phosphate raw materials change, it is usually necessary to readjust the process parameters of lithium iron phosphate. This method is not only more complicated, but also difficult to ensure that the performance of lithium iron phosphate materials is consistent. When synthesizing low-temperature lithium iron phosphate materials by hydrothermal method, high-temperature and high-pressure containers will be used in the synthesis process, which is dangerous.
[0004] Therefore, it is of great significance to find a method to improve the low-temperature performance of lithium iron phosphate batteries. Summary of the invention
[0005] In order to solve the defects existing in the prior art, the present invention provides a porous iron phosphate, lithium iron phosphate and a preparation method thereof. The preparation process and product quality of iron phosphate have a direct impact on the performance, quality, cost, etc. of lithium iron phosphate positive electrode materials. Researching an iron phosphate product with low-temperature characteristics will greatly reduce the cost of lithium iron phosphate companies to study the low-temperature performance of materials. To this end, the first purpose of the present invention is to provide a porous iron phosphate and a preparation method thereof, and by controlling the process conditions of iron phosphate, iron phosphate with rich pores and high specific surface area is obtained. The second purpose of the present invention is to provide a low-temperature lithium iron phosphate and a preparation method thereof, using the porous iron phosphate as a raw material, and through a carbon thermal reduction method, a lithium iron phosphate positive electrode material with excellent low-temperature performance and stability is obtained.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a porous iron phosphate, comprising the following steps:
[0008] (1) mixing a phosphorus source, an oxidant, and an iron source to react to obtain a slurry a;
[0009] (2) filtering and separating the slurry a to obtain a filter cake b;
[0010] (3) After the filter cake b is slurried, phosphoric acid is added so that the molar ratio of Fe to P in the slurry is 0.96 to 0.99, and the pH of the system is adjusted to 1.0 to 1.5 and then crystallized to obtain slurry c;
[0011] (4) Filter the slurry c, wash it again, dry it, and calcine it to obtain the product.
[0012] Preferably, the phosphorus source is selected from one or more of ammonium dihydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, potassium phosphate, potassium dihydrogen phosphate and dipotassium hydrogen phosphate.
[0013] Preferably, the iron source is ferrous sulfate or ferric sulfate.
[0014] Preferably, the amount of the oxidant added in step (1) is to oxidize Fe 2+ 100% to 200% of the required theoretical amount.
[0015] Preferably, in the step (1), the molar ratio of Fe / P in the iron source and the phosphorus source is 1.0 to 1.20.
[0016] Preferably, the reaction temperature in step (1) is 20-70°C.
[0017] Preferably, the aging time after the reaction in step (1) is 0.5 to 4 hours.
[0018] Preferably, in step (3), water is used for slurrying, and the amount of water used is 2 to 4 times the mass of the filter cake b.
[0019] Preferably, the crystallization temperature in step (3) is 90-98° C., and the aging time after crystallization is 2-8 hours.
[0020] Preferably, the reagent for adjusting the pH of the system in step (3) is selected from any one or more of sulfuric acid, hydrochloric acid and nitric acid.
[0021] Preferably, the pulping water used in the re-pulping washing in step (4) is 10 to 20 times the mass of the pulp after filtration.
[0022] In a second aspect, the present invention provides a pore-rich iron phosphate product prepared by the above preparation method.
[0023] Preferably, the BET of the porous iron phosphate product is 8.5 to 15 m 2 / g.
[0024] In a third aspect, the present invention provides a lithium iron phosphate product prepared from the pore-rich iron phosphate product.
[0025] Preferably, the BET of the lithium iron phosphate product is 10 to 16 m 2 / g.
[0026] In a fourth aspect, the present invention provides a method for preparing lithium iron phosphate, comprising: mixing the pore-rich iron phosphate product with a carbon source and a lithium source, and then grinding, spraying, sintering, and crushing to obtain the result.
[0027] The beneficial effects of the present invention are:
[0028] In the preparation process of the porous iron phosphate of the present invention, the molar ratio of Fe to P in the crystallization stage, the pH value and the aging time are comprehensively regulated to obtain an iron phosphate product with rich pores and high specific surface area, and the iron phosphate component is uniform and highly active.
[0029] The present invention uses porous iron phosphate as a raw material for preparing lithium iron phosphate, and can prepare lithium iron phosphate products with excellent low-temperature performance through conventional synthesis processes and auxiliary materials. The lithium iron phosphate positive electrode material of the present invention can withstand low-temperature conditions of -40°C after testing. This avoids enterprises spending a lot of time researching the preparation process of lithium iron phosphate with excellent low-temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the iron phosphate prepared in Example 1;
[0031] Figure 2 This is a SEM image of the iron phosphate prepared in Example 6;
[0032] Figure 3 This is a SEM image of the iron phosphate prepared in Comparative Example 1;
[0033] Figure 4 This is a SEM image of the lithium iron phosphate prepared in Example 1;
[0034] Figure 5 This is a SEM image of the lithium iron phosphate prepared in Example 6;
[0035] Figure 6 This is the SEM image of the lithium iron phosphate prepared in Comparative Example 1. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the technical solution of the invention, the present invention is further described in detail below in conjunction with specific implementation methods.
[0037] In order to obtain iron phosphate with rich pores and high specific surface area to realize the preparation of low-temperature lithium iron phosphate, the present invention first provides a method for preparing porous iron phosphate, comprising the following steps:
[0038] (1) mixing a phosphorus source, an oxidant, and an iron source to react to obtain a slurry a;
[0039] (2) filtering and separating the slurry a to obtain a filter cake b;
[0040] (3) After the filter cake b is slurried, phosphoric acid is added so that the molar ratio of Fe to P in the slurry is 0.96 to 0.99, and the pH of the system is adjusted to 1.0 to 1.5 and then crystallized to obtain slurry c;
[0041] (4) Filter the slurry c, wash it again, dry it, and calcine it to obtain the product.
[0042] The phosphorus source of the present invention is selected from one or more of ammonium dihydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, potassium phosphate, potassium dihydrogen phosphate and dipotassium hydrogen phosphate.
[0043] The iron source of the present invention is ferrous sulfate or ferric sulfate. During the calcination process, the sulfate decomposes and overflows in the form of gas to form an iron phosphate product with a porous morphology.
[0044] The oxidant described in the present invention can be any oxidant in the art that can oxidize divalent iron ions. Preferably, the amount of the oxidant added in step (1) is to oxidize Fe 2+ 100% to 200% of the required theoretical amount.
[0045] Preferably, in the step (1), the molar ratio of Fe / P in the iron source and the phosphorus source is 1.0 to 1.20.
[0046] Preferably, the reaction temperature in step (1) is 20-70°C.
[0047] Preferably, the aging time after the reaction in step (1) is 0.5 to 4 hours.
[0048] Preferably, in step (3), water is used for slurrying, and the amount of water used is 2 to 4 times the mass of the filter cake b.
[0049] In step (3) of the present invention, the molar ratio of Fe to P in the slurry needs to be adjusted to 0.96 to 0.99. Exemplarily, the molar ratio of Fe to P in the slurry is adjusted to any one of 0.96, 0.97, 0.99 or a value between the two. If it exceeds the limited range of the present invention, the composition of the ferric phosphate product will be impure.
[0050] Preferably, the crystallization temperature in step (3) is 90-98°C, and the aging time after crystallization is 2-8h. 90-98°C is the optimal crystallization temperature. If it deviates from this range, the obtained ferric phosphate product is impure and has poor activity. Prolonging the aging time is beneficial to improving the crystallinity of the ferric phosphate product and ensuring the uniformity of each component, but if the time is too long, the improvement effect is not obvious and the production cost of the enterprise is increased.
[0051] Preferably, the reagent for adjusting the pH of the system in step (3) is selected from any one or more of sulfuric acid, hydrochloric acid, and nitric acid. Exemplarily, step (3) adjusts the pH of the system to any one of 1.0, 1.3, 1.5 or a value between the two. The regulation of the pH of the crystallization stage directly affects the overall morphology of the iron phosphate. For example, in Example 1, sulfuric acid is used for regulation, and the overall morphology is spherical iron phosphate particles. In Example 6, hydrochloric acid is used to regulate the pH, and the overall particle morphology is relatively dispersed. The iron phosphate with a porous morphology provides original nano primary particles for the synthesis of low-temperature lithium iron phosphate, making the low-temperature lithium iron phosphate material easy to synthesize. Within the pH limit range of the present invention, a porous iron phosphate with a large specific surface area can be obtained. If the pH range exceeds the limit range, the resulting morphology is quite different, and it is difficult to obtain uniform and consistent original nano primary particles, which is manifested as poor activity of the iron phosphate. It is difficult to obtain a lithium iron phosphate product with good low-temperature performance using the existing lithium iron phosphate synthesis process.
[0052] Preferably, the pulping water used in the re-pulping washing in step (4) is 10 to 20 times the mass of the pulp after filtration.
[0053] In a second aspect, the present invention provides a pore-rich iron phosphate product prepared by the above preparation method.
[0054] Preferably, the BET of the porous iron phosphate product is 8.5 to 15 m 2 / g.
[0055] The present invention uses the porous iron phosphate as a raw material and obtains a stable lithium iron phosphate positive electrode material with excellent low temperature performance through a carbothermal reduction method. In a third aspect, the present invention provides a lithium iron phosphate product prepared from the porous iron phosphate product.
[0056] Preferably, the BET of the lithium iron phosphate product is 10 to 16 m 2 / g.
[0057] In a fourth aspect, the present invention provides a method for preparing lithium iron phosphate, comprising: mixing the pore-rich iron phosphate product with a carbon source and a lithium source, and then grinding, spraying, sintering, and crushing to obtain the result.
[0058] The above is a detailed description of the technical solution of the present invention, and the following is an embodiment of the present invention.
[0059] Example 1
[0060] This embodiment provides a method for preparing porous iron phosphate, the steps are as follows:
[0061] (1) A phosphorus source is prepared by mixing monoammonium phosphate and ammonium phosphate solution. The phosphorus source concentration is expressed as single substance P, and the mass fraction of the P source is 5.2%.
[0062] (2) An iron source is prepared using ferrous sulfate heptahydrate solution. The iron source concentration is expressed as elemental Fe, and the mass fraction of the Fe source is 7.5%.
[0063] (3) According to the ratio of nFe / P=1.03, 2329g of phosphorus source and hydrogen peroxide (the amount of hydrogen peroxide added is the amount of Fe 2+ 100-200% of the required theoretical amount) was added to 3000g of iron source for co-precipitation reaction, the reaction temperature was controlled at 60°C, and aged for 1h to obtain slurry a.
[0064] (4) Slurry a is filtered and separated, and then re-slurried and washed, and then filtered and separated to obtain a wet-base filter cake b.
[0065] (5) The wet-base filter cake b was slurried with pure water, the amount of water used was twice that of the wet-base filter cake b, 35.1 g of 85% phosphoric acid was added to the slurry to make nFe / P in the slurry = 0.97, and 62 g of 98% sulfuric acid was added to continue to adjust the pH to 1.3, the temperature was raised to 95°C, and aged for 8 hours to obtain slurry c.
[0066] (6) Filter and separate the slurry c obtained in step (5) to obtain the dihydrated iron phosphate semi-finished product d, and re-slurry and wash the dihydrated iron phosphate semi-finished product d, with the slurrying water being 20 times that of the dihydrated iron phosphate semi-finished product d; and then filter and separate to obtain the high-purity dihydrated iron phosphate semi-finished product e.
[0067] (7) The high-purity dihydrate ferric phosphate semi-finished product e obtained in step (6) is dried to remove free water, and then calcined at 580° C. for 2 h to remove crystal water to obtain a porous ferric phosphate product.
[0068] The prepared iron phosphate product is used to prepare low-temperature lithium iron phosphate, and the steps are as follows:
[0069] (8) Take 1000 g of the porous iron phosphate product obtained in step (7), lithium carbonate (lithium to iron ratio 1.03), anhydrous glucose (7.5% of the mass of iron phosphate), PEG6000 (4.5% of the mass of iron phosphate), and titanium dioxide (0.2% of the mass of iron phosphate), and add pure water to prepare a slurry f with a solid content of 35%.
[0070] (9) Grind the slurry f obtained in step (8) to control the grinding particle size to D 50 =500nm, and the ground slurry g is obtained. The slurry g is sprayed and granulated. During spraying, the inlet air temperature is set to 250°C, the atomizer is 50Hz, the feed frequency is adjusted, and the exhaust air temperature is controlled to 105°C to obtain the lithium iron phosphate precursor h.
[0071] (10) Take the precursor h prepared in step (9), a total of 600 g, and put it into a sagger. Set the heating rate to 2°C / min, the sintering temperature to 750°C, and the holding time to 9.5 h to obtain a sintered material.
[0072] (11) The sintered material obtained in step (10) is subjected to air flow pulverization, and the pulverized particle size is controlled to be D 50 =1.0~1.4μm, and obtain the finished lithium iron phosphate product.
[0073] Example 2
[0074] The same as Example 1, except that: in step (5), 25.4 g of 85% phosphoric acid is added to the slurry to make nFe / P in the slurry = 0.99, and 43 g of 98% sulfuric acid is added to continue to adjust the pH to 1.5.
[0075] Example 3
[0076] The same as Example 1, except that: in step (5), 85 g of 98% sulfuric acid is added to continue adjusting the pH to 1.0.
[0077] Example 4
[0078] The same as Example 1, except that in step (5), 39.2 g of 85% phosphoric acid is added to the slurry to make nFe / P in the slurry = 0.96.
[0079] Example 5
[0080] Same as Example 1, except that the aging time in step (5) is 2 hours.
[0081] Example 6
[0082] The same as Example 1, except that in step (5), 70 g of 36% hydrochloric acid is added to the slurry, and the pH is continuously adjusted to 1.3.
[0083] Comparative Example 1
[0084] The same as Example 1, except that in step (5), 107 g of 98% sulfuric acid is added to continue adjusting the pH to 0.8.
[0085] Comparative Example 2
[0086] The same as Example 1, except that in step (5), 8.9 g of 85% phosphoric acid is added to the slurry to make nFe / P in the slurry = 1.01.
[0087] Effect Example 1 Morphology Characterization of Porous Iron Phosphate
[0088] Figure 1 This is the SEM image of the iron phosphate prepared in Example 1. Figure 2 This is the SEM image of the iron phosphate prepared in Example 6. Figure 3 This is the SEM image of the iron phosphate prepared in Comparative Example 1.
[0089] from Figure 1 , Figure 2 and Figure 3 It can be seen that the iron phosphates prepared in the embodiments of the present invention are all porous and have a high specific surface area. Under the conditions of Example 1, it is easier to obtain a porous iron phosphate morphology with a high specific surface area. In Example 6, the pH of the crystallization slurry is adjusted with hydrochloric acid under the same conditions, and the specific surface area of the obtained iron phosphate is also relatively high, but the overall morphology is different from that of Example 1, and the overall particles are relatively dispersed. This is because the use of different types of acids to control the pH in the crystallization stage will directly affect the overall morphology of the iron phosphate. Comparative Example 1 exceeds the control range of pH adjustment, and the resulting iron phosphate morphology directly loses the porous characteristics.
[0090] Effect Example 2 Index of Porous Iron Phosphate
[0091] The physical and chemical indicators of the iron phosphate prepared in the examples and comparative examples are shown in Table 1.
[0092] Table 1
[0093] Test subjects Fe% P% nFe / P <![CDATA[D 50 μm]]> <![CDATA[D 99 μm]]> <![CDATA[BETm 2 / g]]> Example 1 36.56 20.73 0.978 2.35 68.48 14.7 Example 2 36.45 20.65 0.979 3.35 59.76 9.6 Example 3 20.68 36.75 0.986 4.67 62.42 12.3 Example 4 20.92 36.24 0.961 5.78 87.23 8.48 Example 5 20.49 36.29 0.982 3.53 49.38 10.39 Example 6 36.52 20.60 0.983 1.80 55.30 12.70 Comparative Example 1 36.64 20.52 0.990 1.68 46.06 5.21 Comparative Example 2 36.85 20.39 1.02 1.63 36.21 12.71
[0094] Effect Example 3 Electrochemical Performance Test of Low-Temperature Lithium Iron Phosphate
[0095] The lithium iron phosphate products obtained in the embodiment and the comparative example were assembled into button batteries, and the low temperature performance was tested in a low temperature constant temperature cabinet, and the results are shown in Table 2. The test conditions were charging at 0.1C at room temperature, and discharging at 1C at -20°C, 0.3C at -35°C, and 0.5C at -40°C.
[0096] Table 2
[0097]
[0098]
[0099] It can be seen from Table 1 and Table 2 that the iron phosphate products prepared in Examples 1 to 6 of the present invention can obtain iron phosphate with a higher specific surface area by comprehensively regulating the nFe / P, pH and aging time of the crystallization slurry, and the obtained iron phosphate component is uniform and has high activity. The synthesized lithium iron phosphate positive electrode material using the iron phosphate products prepared in Examples 1 to 6 as raw materials has excellent low-temperature performance. For the iron phosphate product prepared in Comparative Example 1, the pH of the crystallization slurry is too low, and the specific surface area of the obtained iron phosphate is too low, making it difficult to prepare a lithium iron phosphate positive electrode material with excellent low-temperature performance. For the iron phosphate product prepared in Comparative Example 2, the nFe / P of the crystallization slurry exceeds the control range, and the obtained iron phosphate component is impure and has poor activity, making it equally difficult to prepare a lithium iron phosphate positive electrode material with excellent low-temperature performance.
[0100] Effect Example 4 Morphology Characterization of Lithium Iron Phosphate
[0101] Figure 4 This is a SEM image of the lithium iron phosphate prepared in Example 1. Figure 5 This is a SEM image of the lithium iron phosphate prepared in Example 6. Figure 6 This is the SEM image of the lithium iron phosphate prepared in Comparative Example 1.
[0102] from Figure 4 , Figure 5 and Figure 6 It can be seen that the primary particles of the synthesized lithium iron phosphate are finer and more uniform when the iron phosphate obtained under the conditions of Example 1 is used as the raw material, and the path of lithium ion deintercalation is shorter, which is more conducive to the low-temperature performance of the material. When the iron phosphate obtained under the conditions of Example 6 is used as the raw material, some primary particles of the synthesized lithium iron phosphate are melted and grown, which makes the low-temperature performance of the material worse than that of Example 1. When the iron phosphate obtained under the conditions of Comparative Example 1 is used as the raw material, a large number of primary particles of the synthesized lithium iron phosphate are melted and grown, which makes the low-temperature performance of the material poor.
[0103] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing porous iron phosphate, characterized in that: The following steps are involved: (1) mixing a phosphorus source, an oxidant, and an iron source to react to obtain a slurry a; (2) filtering and separating the slurry a to obtain a filter cake b; (3) After the filter cake b is slurried, phosphoric acid is added so that the molar ratio of Fe to P in the slurry is 0.96 to 0.99, and the pH of the system is adjusted to 1.0 to 1.5 and then crystallized to obtain slurry c; (4) Filter the slurry c, wash it again, dry it, and calcine it to obtain the product.
2. The preparation method according to claim 1, characterized in that: The phosphorus source is selected from one or more of ammonium dihydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, potassium phosphate, potassium dihydrogen phosphate and dipotassium hydrogen phosphate.
3. The preparation method according to claim 1, characterized in that: The iron source is ferrous sulfate or ferric sulfate.
4. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of Fe / P in the iron source and the phosphorus source is 1.0 to 1.
20.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step (3), water is used for slurrying, and the amount of water used is 2 to 4 times the mass of the filter cake b.
6. The preparation method according to any one of claims 1 to 4, characterized in that: The crystallization temperature in step (3) is 90-98° C., and the aging time after crystallization is 2-8 hours.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The reagent for adjusting the pH of the system in step (3) is selected from any one or more of sulfuric acid, hydrochloric acid and nitric acid.
8. A porous iron phosphate product prepared by the preparation method according to any one of claims 1 to 7.
9. A lithium iron phosphate product prepared from the porous iron phosphate product according to claim 8.
10. A method for preparing lithium iron phosphate, characterized in that: include: The porous iron phosphate product according to claim 8 is mixed with a carbon source and a lithium source, and then ground, sprayed, sintered and crushed to obtain the product.